Retained earnings and foreign portfolio ownership: Implications for the current account debate - Stefan Goldbach; Philipp Harms; Axel Jochem; Volker Nitsch; Alfons J. Weichenrieder (Leibniz Institute for Financial Research SAFE, 2023)
In some countries, a sizable fraction of savings is derived from corporate savings. Although larger, traded corporations are often co-owned by foreign portfolio investors, current international accounting standards allocate all corporate savings to the host country. This paper suggests a framework to correct for this misleading attribution and applies this concept to Germany. For the years 2012 to 2020, our corrections retrospectively reduce German savings and consequently the German current account surplus by, on average, exteuro11.5bn annually. This amounts to approximately five percent of Germany's average official current account surplus ( exteuro226.6bn) across these years.
Keywords: F32; E21; 330; current account; balance of payments; corporate savings; retained earnings; foreign portfolio investment; Germany